Understanding interactive effects between habitat configuration and pesticide use for pollination: towards better informed landscape management - Swantje Gebhardt; Jerry van Dijk; Marjolein E. Lof; Martin J. Wassen; Martha Bakker (Ecological Processes)
Abstract Background The restoration of natural landscape elements is a frequently adopted pathway to improve wild pollinator abundance, diversity, and their pollination services in intensively used agricultural landscapes. However, pollinators in the intended refuges can become exposed to agrochemicals when foraging in surrounding agricultural fields. In order to effectively design pollinator conservation measures such as habitat restoration or pesticide reduction schemes, the effect of land use configuration on pesticide exposure and pollination service requires further investigation. Methods We developed a pollination model that extends existing approaches by simulating both pollination flights and concurrent pollinator exposure to toxic pesticides, enabling the estimation of pesticide impacts on pollination services. We calculated pollination service and pollinator health for a set of artificial landscapes, which varied in the percentage of pollinator habitat and agriculture, in the clustering of these land uses, as well as in the pollinator mortality hazard arising from the pesticides applied on agriculture. Results Our results show that in landscapes with less than 10% habitat and highly toxic pesticides, pollination services are mostly safeguarded by compact patches of habitat, as this configuration shelters more habitat from pesticide exposure. With increasing habitat amount or with pesticide applications causing less than 50% mortality in pollinators, more dispersed patches of habitat achieve a better pollination service for the landscape. We further tested the effect of pesticide application for different foraging ranges in a more realistic land use scenario. For pollinators with shorter foraging ranges, pesticide exposure from the immediate surroundings determines the achieved pollination. For species with longer foraging ranges, the availability of resources and the application of pesticides at landscape scale controls the pollination. Conclusion Our study highlights the importance of assessing spatial configuration effects on pesticide exposure for local pollinators. By applying these insights, land managers can devise land use arrangements to protect pollinator habitats and establish buffer zones to support pollinator activity in pesticide-intensive landscapes. As current guidelines largely lack spatially-explicit measures, we suggest to direct future research and policies towards the underlying spatial processes and their facilitation on parcel, farm, and landscape scale.